2019
DOI: 10.1111/jmwh.12984
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postpartum Contraception: Intrauterine Device Insertion

Abstract: Insertion of an intrauterine device (IUD) in the immediate postpartum period is a safe, evidence-based form of contraception appropriate for most women. Despite the higher risk of expulsion as compared with interval insertion, the benefits of insertion in the immediate postpartum period are significant and include improved rates of contraception continuance and reduced instances of short interval birth. Through shared decision making, midwives and other clinicians can assist women in clarifying their reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…Method continuation in the current study was found to be high (86%) at one year of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks post-delivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 83%
“…Method continuation in the current study was found to be high (86%) at one year of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks post-delivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 83%
“…Immediate postpartum LARC refers to either an intrauterine device (IUD; either copper‐ or levonorgestrel‐containing devices) or subdermal etonogestrel implant that is inserted any time after placental expulsion up to 72 hours postpartum regardless of mode of birth . These methods are widely endorsed as safe contraceptive options, with very few contraindications, for those who wish to prevent pregnancy after birth .…”
Section: Immediate Postpartum Larc In the United Statesmentioning
confidence: 99%
“…Emerging guidelines and quality measures emphasize the efficacy of immediate postpartum LARC methods as first‐line contraception, potentially enabling many patients to meet their postpartum reproductive goals . However, although remaining enthusiastic about the potential, authors in the fields of family planning, bioethics, and health policy have cautioned against coercion and have encouraged clinicians to adopt a reproductive justice framework when approaching LARC policies and provision of care .…”
Section: Immediate Postpartum Larc In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine contraceptive device (IUD) is one of the most effective methods for family planning [1]. Available evidence suggest that the timing of IUD insertion immediately postpartum has important implications on acceptance, complications and continuation of the method [1][2][3]. Moreover, studies have shown that the immediate postpartum period provides an ample chance for a convenient and costeffective contraceptive option particularly in settings where women do not usually return for follow-up visits because of distance or socioeconomic reasons [1,2].…”
Section: Introductionmentioning
confidence: 99%